Feasibility Study of Daily Test Items for 5th Grade IPAS Based on Bloom's Taxonomy in Elementary School - Rosmawati, Eka; Wulandari, Bunga Ayu; Widowati, Atri (Papanda Publisher, 2025)
This study aims to analyze the feasibility of the fifth-grade IPAS daily test questions at SD Negeri 153/X Harapan Makmur based on Bloom’s Taxonomy. This research employs a qualitative descriptive method using document analysis, interviews, and observations.